ROLE OF AR AND VR IN THE REALM OF TECHNICAL EDUCATION - Shahabuddin, Syed Khurram; Chandra, Dimple; Asagar, Mirza Shahzan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In recent years, the primary research subjects involve for improving the lives of future generation youngsters to include excellence and creativity in the existing pedagogical system. Virtual reality plays an important part in introducing new educational ideas. To enhance the quality of teaching in aspects of relevant and interactive learning, the recent trend in educational technology is mostly cantered on e-learning and mobile-based learning approaches. Virtual reality is now widely utilised in a variety of fields, including education, healthcare, training, and entertainment. This study paper provides an overview and influence of virtual reality on the pedagogical sector, as well as its current and future aspects.